Forming induced wrinkling of composite laminates: A numerical study on wrinkling mechanisms. (February 2016) - Sjölander, J.; Hallander, P.; Åkermo, M.
Abstract: When manufacturing composite aircraft components consisting of uni-directional prepreg laminates, Hot Drape Forming (HDF) is sometimes used. One issue with HDF is that, in contrast to hand lay-up where normally only one ply is laid up at a time, multiple plies are formed together. This limits the in-plane deformability of the stack, thus increasing the risk of out-of-plane wrinkling during forming. In this paper mechanisms responsible for creating different types of wrinkles are explained. It is shown through simulations how the wrinkles are created as a result of interaction between two layers with specific fibre directions or due to compression of the entire stack. The simulations are compared to experimental results with good agreement.